Erasing the extinct: the hunt for Caribbean monk seals and museum collection practices - Dolly Jørgensen (História, Ciências, Saúde: Manguinhos, 2022)
Abstract The Caribbean monk seal (Monachus tropicalis), the only seal species native to Central America, was declared extinct in 2008, with the last confirmed sighting in 1952. This species historically had a broad range throughout the gulf of Mexico. This article discusses the history of Western science on the monk seal, from its first recorded sighting by a Western colonizer in 1492 to scientific collection in the 1800s and 1900s, as a history of the erasure of this species. Museum practices of collecting and displaying Caribbean monk seals have directly contributed to this erasure, and ways of writing a new history by giving the Caribbean monk seal the capacity to refuse erasure are suggested.